Method of forming carbon-silicon composite material on current collector

JP2024173951A5Inactive Publication Date: 2025-01-09ENEVATE CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024162327
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-03-28
Filing Date
2024-09-19
Publication Date
2025-01-09
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for forming carbon-silicon composites on current collectors in lithium ion batteries face challenges such as the reaction of silicon and carbon with metal current collectors, leading to adhesion issues and damage, which affects the integrity and conductivity of the electrodes.

Method used

A method involving pyrolyzing a mixture of carbon precursor and silicon particles on a current collector, such as stainless steel or tungsten, to form a carbon-silicon composite that adheres well without significant reaction, using a polymer or carbon coating to prevent metal silicide and carbide formation.

Benefits of technology

The method allows for high-energy density electrodes with improved adhesion to the current collector, reduced handling of fragile electrodes, and cost-effective, rapid processing, maintaining electrical conductivity while minimizing deleterious reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a method of forming an electrode capable of being rolled without failures, such as cracks, brakes, mechanical failures, etc.SOLUTION: In some embodiments, the method can include providing a current collector. The method can also include providing a mixture on the current collector. The mixture can include a precursor and silicon particles. The method can further include pyrolysing the mixture on the current collector to convert the precursor into one or more types of carbon phases to form a composite material and to adhere the composite material to the current collector. The one or more types of carbon phases can be a substantially continuous phase with the silicon particles distributed throughout the composite material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to electrodes, electrochemical cells, and methods of forming electrodes and electrochemical cells. In particular, the present disclosure relates to methods of forming carbon-silicon composite materials on current collectors. [Background technology]

[0002] Lithium ion batteries usually include a separator and / or electrolyte between the anode and cathode. In one class of batteries, the separator, cathode and anode materials are individually formed into sheets or films. The sheets of cathode, separator and anode are then stacked or rolled together with a separator separating the cathode and anode (e.g., electrode) to form a battery. In order for the cathode, separator and anode to be rolled, each sheet must be sufficiently deformable or flexible to be rolled without damage such as cracks, brakes, mechanical defects, etc. A typical electrode includes a layer of electrochemically active material on a conductive metal (e.g., aluminum and copper). For example, carbon can be deposited on a current collector with an inert binder material. Carbon is often used because it has good electrochemical properties and is also electrically conductive. The electrodes can be rolled or cut into sections that are then layered into a stack. In the stack, the electrochemically active material is arranged alternately on either side of the separator. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] U.S. Patent Application No. 13 / 008,800 [Patent Document 2] U.S. Patent Application Serial No. 13 / 601,976 [Patent Document 3] U.S. Patent Application Serial No. 13 / 799,405 [Patent Document 4] U.S. Patent Application Serial No. 13 / 333,864 [Patent Document 5] U.S. Patent Application Serial No. 13 / 796,922 Summary of the Invention [Means for solving the problem]

[0004] In an embodiment, a method of forming an electrode is provided. The method may include providing a current collector. The method may also include dispensing a mixture onto the current collector. The mixture may include a precursor and silicon particles. The method may further include pyrolyzing the mixture to convert the precursor into one or more carbon phases to form a composite material on the current collector, and adhering the composite material to the current collector. The one or more carbon phases may be a substantially continuous phase that includes silicon particles distributed throughout the composite material.

[0005] In various embodiments, providing a current collector can include providing a current collector comprising stainless steel. For example, providing a current collector can include providing a stainless steel foil. In another example, providing a current collector can include providing a clad foil comprising stainless steel on at least one side of the clad foil. Applying the mixture onto the current collector can include applying the mixture onto at least one side of a clad foil comprising stainless steel.

[0006] In various embodiments, providing a current collector can include providing a current collector comprising tungsten. For example, providing a current collector can include providing a tungsten foil. In another example, providing a current collector can include providing a clad foil comprising tungsten on at least one side of the clad foil. Applying the mixture onto the current collector can include applying the mixture onto at least one side of a clad foil comprising tungsten.

[0007] In various embodiments, providing a current collector may include providing a current collector coated with a polymer on at least one side of the current collector. In some such embodiments, providing the mixture may include providing the mixture on at least one side of the current collector including the polymer. In some embodiments, the polymer and the precursor may be the same material. The precursor may include a polyamideimide, a polyamic acid, a polyimide, a phenolic resin, or an epoxy resin.

[0008] In some embodiments, providing a current collector may include providing a current collector coated with a carbon film on at least one surface of the current collector. In some such embodiments, providing a current collector coated with a carbon film may include providing a carbon precursor on at least one surface of the current collector and pyrolyzing the carbon precursor to form a carbon film. The carbon precursor may include a polyamideimide, a polyamic acid, a polyimide, a phenolic resin, or an epoxy resin. In some cases, applying the mixture may include applying the mixture on at least one surface of a current collector including a carbon film.

[0009] In some embodiments, providing the mixture may include providing a slurry including the precursor and silicon particles. Provided the mixture may include slot die coating the mixture onto a current collector. In some embodiments, the method may further include drying the mixture prior to pyrolyzing the mixture.

[0010] The step of providing the mixture may include providing silicon particles such that the composite material contains about 70% by weight to about 90% by weight of silicon particles. In some cases, the step of providing the mixture may further include providing conductive particles in the mixture. In some cases, the step of providing the mixture may include providing graphite in the mixture.

[0011] In various embodiments, the electrode may be an anode. In some embodiments, a battery electrode may be formed by the present method. [Brief description of the drawings]

[0012] [Figure 1] 1A-1C illustrate examples of methods for forming electrodes according to certain embodiments described herein. [Diagram 2] FIG. 1 shows an example of a slurry of carbon precursor and silicon particles coated and dried on a stainless steel foil. [Diagram 3] FIG. 1 shows an example of a pyrolyzed composite material on stainless steel. [Figure 4] 1 is a graph showing plots of discharge capacity as a function of cycle number for various samples. [Diagram 5] 1 is a graph showing a plot of IEC (International Electrotechnical Commission) capacity as a function of cycle number for various samples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] This specification describes certain embodiments of electrodes (e.g., anodes and cathodes) and electrochemical cells that may include carbonized polymers and silicon materials. For example, a mixture that includes a carbon precursor that includes a silicon material may form a composite material. This mixture may include both carbon and silicon, and therefore may be referred to as a carbon-silicon composite, a silicon-carbon composite, a carbon composite, or a silicon composite. This specification also describes certain methods of forming such composite materials on a current collector. The mixture that includes a carbon precursor and a silicon material generally does not pyrolyze directly on the current collector (e.g., a copper or nickel current collector). During the carbonization process (e.g., under heating), the silicon and / or carbon may react directly with the metal current collector (e.g., producing copper or nickel silicides or carbides). The metal silicides or carbides may prevent adhesion of the composite to the current collector and / or may destroy the current collector by converting it to a different material. Various embodiments described herein may advantageously pyrolyze a carbon precursor containing silicon material on a current collector with sufficient adhesion to the current collector and / or with relatively little or no deleterious conversion of the current collector.

[0014] A typical carbon anode electrode includes a current collector, such as a copper sheet. Carbon is deposited on the current collector with an inert binder material. Carbon is often used because it has good electrochemical properties and is also electrically conductive. Anode electrodes used in rechargeable lithium-ion cells typically have a specific capacity of approximately 200 milliamp hours per gram (including metal foil current collector, conductive additives, and binder materials). Graphite, the active material used in most lithium-ion battery anodes, has a theoretical energy density of 372 milliamp hours per gram (mAh / g). In comparison, silicon has a high theoretical capacity of 4200 mAh / g. However, silicon expands by more than 300% upon lithiation. Due to this expansion, anodes containing silicon can expand / contract and lose electrical contact with the rest of the anode. Therefore, silicon anodes should be designed to be able to expand while maintaining good electrical contact with the rest of the electrode.

[0015] US Patent Application No. 13 / 008,800, US Patent Application No. 13 / 601,976, and US Patent Application No. 13 / 799,405, each of which is incorporated herein by reference, describe certain embodiments of carbon-silicon composites using carbonized polymers and silicon materials. The carbonized polymer can act as an expansion buffer for the silicon particles upon cycling so that high cycle life can be achieved. In some embodiments, the resulting electrode can be an electrode that is substantially composed of the active material. For example, in contrast to particulate carbon suspended in a non-conductive binder in one class of conventional lithium ion battery electrodes, the carbonized polymer can form a substantially continuous conductive carbon phase throughout the electrode. Because the polymer can be converted into a conductive, electrochemically active matrix, the resulting electrode can be sufficiently conductive so that in some embodiments, metal foil or mesh current collectors can be omitted, minimized, or reduced. Thus, US Patent Application No. 13 / 008,800, US Patent Application No. 13 / 601,976, and US Patent Application No. 13 / 799,405 disclose certain embodiments of monolithic free-standing electrodes. The electrodes can have high energy densities between about 500 mAh / g and about 3500 mAh / g. This may be due, for example, to 1) the use of silicon, 2) the elimination or significant reduction of metal current collectors, and 3) being entirely or substantially entirely composed of active materials.

[0016] For example, in some applications where current exceeds a certain threshold or additional mechanical support may be desired, a current collector may be preferred. As mentioned above, currently, a mixture containing a carbon precursor and a silicon material is not pyrolyzed directly on a current collector because it is believed that the carbon and / or silicon may react with the metal current collector during the pyrolysis process. To overcome such a problem, the mixture can be first delivered onto a substrate, pyrolyzed, removed from the substrate, and then attached to a current collector. U.S. Patent Application No. 13 / 333,864 and U.S. Patent Application No. 13 / 796,922, each of which is incorporated herein by reference, describe certain embodiments of composite materials that are attached to a current collector using an electrode attachment material.

[0017] The present specification also describes certain embodiments of electrodes including current collectors, electrochemical cells including such electrodes, and methods of forming such electrodes and electrochemical cells. For example, in various embodiments, the electrodes include a composite material attached to a current collector. The electrodes described herein can be used as the anodes of lithium ion batteries. The electrodes can also be used as the cathodes of some electrochemical couples with additional additives. The electrodes can be used in both secondary (e.g., rechargeable) and primary (e.g., non-rechargeable) batteries. Additionally, various embodiments include materials that can adhere well to the current collector and that thermally decompose on the current collector with relatively little or no adverse reactions with the metal current collector.

[0018] FIG. 1 illustrates an example of a method for forming an electrode according to certain embodiments described herein. The method 100 for forming an electrode may include providing a current collector, as shown in block 110. The method 100 may also include dispensing a mixture onto the current collector, as shown in block 120. The mixture may include a precursor (e.g., a carbon precursor) and silicon particles. As shown in block 130, the method 100 may further include pyrolyzing the mixture on the current collector. Decomposing the mixture may convert the precursor into one or more types of carbon phases as a substantially continuous phase with silicon particles distributed throughout the composite material, and may adhere the composite material to the current collector. Thus, various embodiments described herein may pyrolyze a mixture of carbon precursor and silicon particles on the current collector to form a carbon-silicon composite material that adheres to the current collector. Such embodiments may advantageously provide high yields due to reduced handling of fragile electrodes. Such embodiments may also advantageously allow for rapid processing and low costs.

[0019] Without being bound to any particular theory, silicon and / or carbon in the mixture may react with metals in the current collector, such as copper or nickel, and tend to form metal silicides or carbides that prevent adhesion to the current collector and / or destroy the current collector by converting it to a different material. In various embodiments described herein, the formation of metal silicides and / or carbides can be reduced (and / or in some cases avoided) by using a current collector that reduces the possibility of reaction with silicon and / or carbon, allowing the composite material to adhere to the current collector while maintaining the conductive metallic nature of the current collector. Some embodiments may include a step of feeding a mixture of a carbon precursor and a silicon material onto a current collector that includes a material that does not react with silicon and / or carbon and pyrolyzing thereon. For example, instead of using a copper or nickel current collector, some embodiments may include a step of feeding a mixture of a carbon precursor and a silicon material onto a current collector that includes stainless steel, tungsten, or a combination thereof and pyrolyzing thereon. Stainless steel and tungsten do not appear to react with silicon and carbon in the same way as copper and nickel. In another example, some embodiments may include providing a mixture of carbon precursor and silicon material on a current collector that is coated with a layer of polymer or carbon and pyrolyzing thereon. Without being bound to any particular theory, the presence of the coating layer on the current collector may separate the current collector from the silicon and / or carbon in the mixture and reduce and / or possibly avoid the formation of metal silicides and / or carbides. The steps of FIG. 1 will now be described.

[0020] Referring to block 110, a current collector is provided. The current collector provided may include a current collector including stainless steel. In some embodiments, the current collector may include primarily stainless steel. For example, the current collector may include stainless steel metal, e.g., stainless steel foil. In some other embodiments, the current collector may include stainless steel as one of the materials. For example, the current collector may include a clad material including stainless steel, e.g., a clad foil including stainless steel on at least one side of the clad foil (e.g., on one side or on both sides). In some embodiments, the current collector may include primarily tungsten. For example, the current collector may include tungsten metal, e.g., a tungsten foil. In some other embodiments, the current collector may include tungsten as one of the materials. For example, the current collector may include a clad material including tungsten, e.g., a clad foil including tungsten on at least one side of the clad foil (e.g., on one side or on both sides). In another example, the current collector may include a clad material including tungsten on one side and stainless steel on the other side.

[0021] In some embodiments, the current collector may include a polymer coating. For example, the current collector may include a polymer coating on a copper or nickel current collector. In another example, the current collector may include a polymer coating on a stainless steel and / or tungsten current collector. The current collector may be coated with a polymer on at least one side of the current collector. The polymer coating may include any of the precursors described herein, such as a carbon precursor, e.g., a polyamideimide. In some embodiments, the polymer coating may be the same material as the precursors in the mixture. In some other embodiments, the polymer coating may not be the same material as the precursors in the mixture. In various embodiments, the polymer coating may be any of the polymers disclosed herein, including polyamideimide, polyamic acid, polyimide, phenolic resin, epoxy resin, and the like. The thickness of the polymer coating in various embodiments can be any range formed from about 200 nanometers to about 5 microns (e.g., about 200 nm, about 250 nm, about 300 nm, about 400 nm, about 500 nm, about 600 nm, about 700 nm, about 750 nm, about 800 nm, about 900 nm, about 1 micron, about 2 microns, about 3 microns, about 4 microns, about 5 microns, or any value within this range, etc.), or any value within this range.

[0022] In some embodiments, the current collector having the polymer coating can be heat treated prior to further processing (e.g., before the mixture is applied onto the current collector). The heat treatment can produce a carbon-coated current collector through a pyrolysis process. The pyrolysis process can be similar to the process of pyrolyzing the mixture described herein. Thus, in some embodiments, the current collector provided can include a current collector coated with a carbon material (e.g., a carbon film).

[0023] Referring to block 120, the mixture is provided on a current collector. In some embodiments, the mixture may be provided on a current collector, for example, a current collector including stainless steel, tungsten, or a combination thereof. For example, the mixture may be coated (e.g., directly coated in various embodiments) on a stainless steel or tungsten foil. In another example, the mixture may be coated (e.g., directly coated in various embodiments) on at least one side of a clad foil including stainless steel, tungsten, or a combination thereof. The other side of the clad foil may include a different material, including, for example, copper or nickel. In some embodiments, the clad foil may include stainless steel on both sides of the clad foil, tungsten on both sides of the clad foil, or stainless steel on one side of the clad foil and tungsten on the other side of the clad foil. In some such cases, the mixture may be coated on both sides of the clad foil.

[0024] In another example, the mixture can be provided on a current collector that is coated with a polymer, carbon, or a combination thereof on at least one side of the current collector. The mixture can be provided on a side of the current collector that is coated with a polymer, carbon, or a combination thereof. The current collector can be coated with a polymer, carbon, or a combination thereof on both sides (e.g., a polymer coating on both sides of the current collector, a carbon coating on both sides of the current collector, or a carbon coating on one side and a polymer coating on the other side, etc.), and the mixture can be provided on both sides of the current collector. In some cases, the current collector having a polymer coating, a carbon coating, or a combination thereof can include a current collector that includes stainless steel, tungsten, or a combination thereof. However, in some cases, the current collector having a polymer coating, a carbon coating, or a combination thereof does not necessarily include stainless steel, tungsten, or a combination thereof. For example, the current collector having a polymer or carbon coating can include copper or nickel in some embodiments.

[0025] The mixture provided on the current collector may include any of the mixtures described in U.S. Patent Application No. 13 / 008,800, U.S. Patent Application No. 13 / 601,976, and / or U.S. Patent Application No. 13 / 799,405. The mixture may include a variety of different components. The mixture may include one or more precursors. In some embodiments, the precursor is a hydrocarbon compound. For example, the precursor may include polyamideimide, polyamic acid, polyimide, and the like. Other precursors include phenolic resins, epoxy resins, and other polymers. The mixture may further include a solvent. For example, the solvent may be N-methyl-pyrrolidone (NMP). Other possible solvents include acetone, diethyl ether, gamma butyrolactone, isopropanol, dimethyl carbonate, ethyl carbonate, dimethoxyethane, and the like. Examples of precursor and solvent solutions include PI-2611 (HD Microsystems), PI-5878G (HD Microsystems), and VTEC PI-1388 (RBI, Inc.). PI-2611 is comprised of more than 60% n-methyl-2-pyrrolidone and 10-30% s-biphenyl dianhydride / p-phenylenediamine. PI-5878G is comprised of more than 60% n-methylpyrrolidone, 10-30% polyamic acid from pyromellitic anhydride / oxydianiline, and 10-30% aromatic hydrocarbons (petroleum distillates) with 5-10% 1,2,4-trimethylbenzene. In some embodiments, the amount of precursor (e.g., solid polymer) in the solvent is about 10 wt.% to about 30 wt.%.

[0026] The mixture may include silicon particles as described herein. The mixture may include about 5% to about 80% by weight of precursor and greater than 0% to about 90% by weight of silicon particles. Additional materials may also be included in the mixture. As examples, graphite active material, chopped or crushed carbon fibers, carbon nanofibers, carbon nanotubes, and other carbon particles including conductive carbon may be added to the mixture. Conductive particles may also be added to the mixture. Additionally, the mixture may be mixed to homogenize the mixture.

[0027] In some embodiments, the mixture can be cast onto a current collector. In some embodiments, casting includes using gap extrusion, tape casting, or blade casting techniques. Blade casting techniques can include applying a coating to the current collector by using a flat surface (e.g., a blade) that is controlled to be a specific distance above the current collector. The slurry (or liquid) can be applied to the current collector, and the blade can be passed over the slurry to spread the slurry onto the current collector. As the slurry passes through the gap between the blade and the current collector, the thickness of the coating can be controlled by the gap. As the slurry passes through the gap, excess slurry can also be removed. For example, the mixture can be cast onto the current collector. In some embodiments, the mixture can then be dried to remove the solvent. In some cases, the mixture can be dried in a conventional oven. For example, the polyamic acid and NMP solution can be dried at about 110° C. for about 2 hours to remove the NMP solution. In some embodiments, the dried mixture can be further dried or cured. In some embodiments, the mixture can be hot pressed (e.g., sandwiched between graphite plates in an oven). A hot press can be used to dry and keep the dried mixture flat. For example, the dried mixture from the polyamic acid and NMP solution can be hot pressed at about 200° C. for about 8-16 hours. Alternatively, the entire process, including casting and drying, can be performed as a roll-to-roll process using standard film-handling equipment. The dried mixture can be rinsed to remove any solvent or etchant that may remain. For example, deionized (DI) water can be used to rinse the dried mixture. The dried mixture can be cut or mechanically divided into smaller pieces. In some embodiments, the mixture can be coated onto a current collector by a slot-die coating process (e.g., metering a constant or substantially constant mass and / or volume through a set or substantially set gap).FIG. 2 shows an example of a slurry of carbon precursor and silicon particles coated and dried onto a stainless steel foil.

[0028] The mixture is further pyrolyzed, see block 130 of FIG. 1. In various embodiments, pyrolysis can convert the precursor to carbon and adhere the pyrolyzed material to a current collector. For example, after drying the mixture, the material on the current collector can be punched out and pyrolyzed in a furnace. Various ramp rates and final dwell temperatures of pyrolysis can be used to obtain the desired electrode. FIG. 3 shows an example of a pyrolyzed composite on stainless steel. Prior to pyrolysis, these samples were coated on one side, dried, and punched into round shapes.

[0029] In some embodiments, the mixture is pyrolyzed in a reducing atmosphere. For example, an inert atmosphere, vacuum, and / or flowing argon, nitrogen, or helium gas can be used. In some embodiments, the mixture is heated to about 900° C. to about 1350° C. For example, polyimide formed from polyamic acid can be carbonized at about 1175° C. for about 1 hour. In some embodiments, the heating and / or cooling rate of the mixture is about 10° C. / min. A holder can be used to hold the mixture in a particular geometry. The holder can be graphite, metal, etc. In some embodiments, the mixture is flattened. After pyrolysis of the mixture, tabs can be attached to the pyrolyzed material to form electrical contacts. For example, nickel, copper, or alloys thereof can be used for the tabs.

[0030] In some embodiments, one or more of the methods described herein are continuous processes. For example, casting, drying, possibly curing, and pyrolysis can be performed in a continuous process. For example, the mixture can be coated on a current collector, dried, and pyrolyzed. The mixture can be dried while a cylinder that creates a film is rotating. The dried mixture on the current collector can be transferred as a roll and fed to another machine for further processing. Extrusion techniques and other film-making techniques known in the industry can also be utilized prior to the pyrolysis step.

[0031] Pyrolysis of the precursor results in a carbon material (e.g., at least one carbon phase). In some embodiments, the carbon material is hard carbon. In some embodiments, the precursor is any material that can be pyrolyzed to form hard carbon. When the mixture includes one or more additional materials or phases in addition to the carbonized precursor, a composite material can be produced. In particular, as described herein, the mixture can include silicon particles to produce a silicon-carbon (e.g., at least one first phase including silicon and at least one second phase including carbon) or silicon-carbon-carbon (e.g., at least one first phase including silicon, at least one second phase including carbon, and at least one third phase including carbon) composite material.

[0032] Silicon particles can enhance the specific lithium insertion capability of the composite. When silicon absorbs lithium ions, it results in a large volume increase of more than about 300 volume percent, which can cause electrode structure integrity problems. In addition to the problems with volume expansion, silicon is not inherently conductive, but when alloyed with lithium (e.g., lithiation), it becomes conductive. When silicon is delithiated, the surface of the silicon loses electrical conductivity. Furthermore, when silicon is delithiated, the volume decreases, which can cause the silicon particles to lose contact with the matrix. The large change in volume also causes mechanical defects in the silicon particle structure, which in turn causes pulverization. The pulverization and loss of electrical contact has made it difficult to use silicon as an active material in lithium-ion batteries. Reducing the initial size of the silicon particles can prevent further pulverization of the silicon powder as well as minimize the loss of surface electrical conductivity. Furthermore, adding a material to the composite that can elastically deform with the volume change of the silicon particles can reduce the possibility of loss of electrical contact on the silicon surface. For example, the composite material may include carbon, such as graphite, which contributes to the composite's ability to absorb expansion and to the storage capacity of the electrode (e.g., chemically active) as well as the ability to intercalate lithium ions. Thus, the composite material may include one or more types of carbon phases.

[0033] As described herein, silicon can be used as an active material for the cathode or anode to increase the volumetric and gravimetric energy density of lithium-ion batteries. Several types of silicon materials, such as silicon nanopowder, silicon nanofiber, porous silicon, and ball-milled silicon, are possible candidates as active materials for the negative or positive electrodes.

[0034] In some embodiments, all, substantially all, or at least a portion of the silicon particles may have a particle size (e.g., diameter or largest dimension of the particle) of less than about 50 μm, less than about 40 μm, less than about 30 μm, less than about 20 μm, less than about 10 μm, less than about 1 μm, between about 10 nm and about 50 μm, between about 10 nm and about 40 μm, between about 10 nm and about 30 μm, between about 10 nm and about 20 μm, between about 0.1 μm and about 20 μm, between about 0.5 μm and about 20 μm, between about 1 μm and about 20 μm, between about 1 μm and about 15 μm, between about 1 μm and about 10 μm, between about 10 nm and about 10 μm, between about 10 nm and about 1 μm, less than about 500 nm, less than about 100 nm, and about 100 nm. For example, in some embodiments, the average particle size (or average diameter or average maximum dimension) or median particle size (or median size or median maximum dimension) of the silicon particles can be less than about 50 μm, less than about 40 μm, less than about 30 μm, less than about 20 μm, less than about 10 μm, less than about 1 μm, between about 10 nm and about 50 μm, between about 10 nm and about 40 μm, between about 10 nm and about 30 μm, between about 10 nm and about 20 μm, between about 0.1 μm and about 20 μm, between about 0.5 μm and about 20 μm, between about 1 μm and about 20 μm, between about 1 μm and about 15 μm, between about 1 μm and about 10 μm, between about 10 nm and about 10 μm, between about 10 nm and about 1 μm, less than about 500 nm, less than about 100 nm, and about 100 nm. In some embodiments, the silicon particles can have a distribution of particle sizes. For example, at least about 95%, at least about 90%, at least about 85%, at least about 80%, at least about 70%, or at least about 60% of the particles can have a particle size as described herein.

[0035] The amount of silicon provided to the mixture or composite can be greater than 0 weight percent of the mixture and / or composite. In some embodiments, the amount of silicon is greater than about 0 weight percent to about 95 weight percent, greater than about 0 weight percent to about 90 weight percent, greater than about 0 weight percent to about 35 weight percent, greater than about 0 weight percent to about 25 weight percent, about 10 weight percent to about 35 weight percent, at least about 30 weight percent, about 30 weight percent to about 95 weight percent, about 30 weight percent to about 90 weight percent, about 30 weight percent to about 80 weight percent, at least about 50 weight percent, about 50 weight percent to about 95 weight percent, in the range of about 0% to about 95% by weight of the composite material, including about 50% to about 90% by weight, about 50% to about 80% by weight, about 50% to about 70% by weight, at least about 60% by weight, about 60% to about 95% by weight, about 60% to about 90% by weight, about 60% to about 80% by weight, at least about 70% by weight, about 70% to about 95% by weight, or about 70% to about 90% by weight.

[0036] According to certain embodiments described herein, certain micron-sized silicon particles with nanometer surface features can achieve high energy density and can be used in composites and / or electrodes used in electrochemical cells to improve performance during cell cycling. Small particle size silicon (e.g., nanometer range size) can generally enhance the cycle life performance of electrodes. It can also exhibit very high irreversible capacity. However, small particle size can also result in very low volumetric energy density (e.g., for the entire cell stack) due to the difficulty in packing the active material. Large particle size (e.g., micrometer or micron range size) can generally result in high density anode material. However, the expansion of silicon active material can result in poor cycle life due to particle cracking.

[0037] In some embodiments, micron-sized silicon particles can provide good volumetric and gravimetric energy density combined with good cycle life. In some embodiments, to obtain the advantages of both micron-sized silicon particles (e.g., high energy density) and nanometer-sized silicon particles (e.g., good cycle behavior), silicon particles can have an average particle size in the micron range and a surface that includes nanometer-sized features. In some embodiments, silicon particles have an average particle size (e.g., average diameter or average maximum dimension) or median particle size (e.g., median size or median maximum dimension) between about 0.1 μm and about 30 μm or between all values ​​between about 0.1 μm and about 30 μm. For example, in some embodiments, the silicon particles can have an average particle size between about 0.1 μm and about 20 μm, between about 0.5 μm and about 25 μm, between about 0.5 μm and about 20 μm, between about 0.5 μm and about 15 μm, between about 0.5 μm and about 10 μm, between about 0.5 μm and about 5 μm, between about 0.5 μm and about 2 μm, between about 1 μm and about 20 μm, between about 1 μm and about 15 μm, between about 1 μm and about 10 μm, between about 5 μm and about 20 μm, etc. Thus, the average or median particle size can be any value between about 0.1 μm and about 30 μm, such as 0.1 μm, 0.5 μm, 1 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 15 μm, 20 μm, 25 μm, and 30 μm. Nanometer-sized features can include average feature sizes (e.g., average diameters or average maximum dimensions) between about 1 nm and about 1 μm, between about 1 nm and about 750 nm, between about 1 nm and about 500 nm, between about 1 nm and about 250 nm, between about 1 nm and about 100 nm, between about 10 nm and about 500 nm, between about 10 nm and about 250 nm, between about 10 nm and about 100 nm, between about 10 nm and about 75 nm, or between about 10 nm and about 50 nm. The features can include silicon material.

[0038] Further, the silicon particles may have a distribution of particle sizes, for example, at least about 95%, at least about 90%, at least about 85%, at least about 80%, at least about 70%, or at least about 60% of the particles may have a particle size described herein.

[0039] In some embodiments, the silicon particles are at least partially crystalline, substantially crystalline, and / or completely crystalline. Furthermore, the silicon particles may or may not be substantially pure silicon. For example, the silicon particles may be substantially silicon or a silicon alloy. In one embodiment, the silicon alloy comprises silicon as a major component together with one or more other elements.

[0040] Certain embodiments described herein are 2 / g to about 30m 2 / g, about 1m 2 / g to about 25m 2 / g, about 1m 2 / g to about 20m 2 / g, about 1m 2 / g to about 10m 2 / g, approximately 2m 2 / g to about 30m 2 / g, approximately 2m 2 / g to about 25m 2 / g, approximately 2m 2 / g to about 20m 2 / g, approximately 2m 2 / g to about 10m 2 / g, about 3m 2 / g to about 30m 2 / g, about 3m 2 / g to about 25m 2 / g, about 3m 2 / g to about 20m 2 / g, about 3m 2 / g to about 10m 2 / g (for example, about 3m 2 / g to about 6m 2 / g), about 5m 2 / g to about 30m 2 / g, about 5m 2 / g to about 25m 2 / g, about 5m 2 / g to about 20m 2 / g, about 5m 2 / g to about 15m 2 / g, or about 5m 2 / g to about 10m2 / g (eg, using Brunauer Emmet Teller (BET) particle surface area measurements).

[0041] Compared with the silicon particles used in conventional electrodes, the silicon particles described herein generally have a larger average particle size.In some such embodiments, the average surface area of ​​the silicon particles described herein is generally small.Without being bound to any particular theory, the low surface area of ​​the silicon particles described herein may contribute to improved performance of electrochemical cells.

[0042] Advantageously, the silicon particles described herein can enhance the performance of electrochemically active materials, such as improving capacity and / or cycling performance. Moreover, electrochemically active materials having such silicon particles may not be significantly degraded as a result of lithiation of the silicon particles.

[0043] The amount of carbon obtained from the precursor can be about 5% by mass to about 80% by mass, about 5% by mass to about 70% by mass, about 5% by mass to about 60% by mass, about 5% by mass to about 50% by mass, about 5% by mass to about 40% by mass, about 5% by mass to about 30% by mass, about 10% by mass to about 50% by mass, about 10% by mass to about 40% by mass, about 10% by mass to about 30% by mass, about 10% by mass to about 25% by mass, etc. For example, the amount of carbon obtained from the precursor can be about 10% by mass, about 15% by mass, about 20% by mass, about 25% by mass, etc. of the precursor.

[0044] The carbon from the precursor can be hard carbon. Hard carbon can be carbon that does not convert to graphite even when heated above 2800 degrees Celsius. Precursors that melt or flow upon pyrolysis convert to soft carbon and / or graphite with sufficient temperature and / or pressure. Hard carbon can be selected because soft carbon precursors can flow and soft carbon and graphite are mechanically weaker than hard carbon. Other possible hard carbon precursors can include phenolic resins, epoxy resins, and other polymers that have very high melting points or are crosslinked. The amount of hard carbon in the composite can be any of the ranges described herein for the amount of carbon obtained from the precursor. For example, in some embodiments, the amount of hard carbon in the composite may have a value in the range of about 10% to about 25% by weight, about 10% to about 30% by weight, about 10% to about 40% by weight, about 10% to about 50% by weight, about 10%, about 20%, about 30%, about 40%, about 50%, or more than about 50% by weight. In some embodiments, the hard carbon phase is substantially amorphous. In other embodiments, the hard carbon phase is substantially crystalline. In further embodiments, the hard carbon phase includes amorphous and crystalline carbon. The hard carbon phase may be a matrix phase in the composite. The hard carbon may also be embedded in the pores of the silicon-containing additive. The hard carbon may react with a portion of the additive to produce some material at the interface. For example, a silicon carbide layer may be present between the silicon particles and the hard carbon.

[0045] In some embodiments, graphite is one of the types of carbon phases from the precursor. In some embodiments, graphite particles are added to the mixture. Advantageously, graphite can be the electrochemically active material in the battery as well as a resilient, deformable material that can accommodate the volumetric changes of silicon particles. Graphite has low irreversible capacity, making it the preferred active anode material for certain classes of lithium-ion batteries currently on the market. In addition, graphite is softer than hard carbons and can better accommodate the volumetric expansion of silicon additives. In some embodiments, all, substantially all, or at least a portion of the graphite particles can have a particle size (e.g., diameter or maximum dimension) between about 0.5 microns and about 20 microns. In some embodiments, the graphite particles have an average particle size (e.g., average diameter or average maximum dimension) or a median particle size (e.g., median size or median maximum dimension) between about 0.5 microns and about 20 microns. In some embodiments, the graphite particles can have a distribution of particle sizes. For example, at least about 95%, at least about 90%, at least about 85%, at least about 80%, at least about 70%, or at least about 60% of the particles can have a particle size described herein. In some embodiments, the composite material can include graphite particles in an amount from greater than 0% to less than about 80% by weight, including from 40% to about 75%, from about 5% to about 30%, from 5% to about 25%, from 5% to about 20%, or from 5% to about 15% by weight.

[0046] In some embodiments, conductive particles, which may be electrochemically active, are added to the mixture. Such particles may allow both more conductive composites and mechanically deformable composites that can accommodate larger volume changes to occur upon lithiation and delithiation. In some embodiments, all, substantially all, or at least a portion of the conductive particles may have a particle size (e.g., diameter or maximum dimension) between about 10 nanometers and about 7 millimeters. In some embodiments, the average particle size (e.g., average diameter or average maximum dimension) or median particle size (e.g., median size or median maximum dimension) of the conductive particles is between about 10 nm and about 7 millimeters. In some embodiments, the conductive particles may have a distribution of particle sizes. For example, at least about 95%, at least about 90%, at least about 85%, at least about 80%, at least about 70%, or at least about 60% of the particles may have a particle size described herein.

[0047] In some embodiments, the mixture comprises conductive particles in an amount of from greater than 0% to about 80% by weight. In some embodiments, the composite comprises from about 45% to about 80% by weight. The conductive particles can be conductive carbon, including carbon black, carbon fiber, carbon nanofiber, carbon nanotubes, and the like. Many carbons that are not electrochemically active but are considered conductive additives become active once pyrolyzed in the polymer matrix. The conductive particles can also be metals or alloys, including copper, nickel, or stainless steel.

[0048] The material obtained after pyrolysis of the precursor is a composite material that adheres to the current collector. The composite material may be a self-supporting monolithic structure, e.g., a self-supporting composite film, so that the current collector can provide additional mechanical support. For example, the carbonized precursor can produce an electrochemically active structure that holds the composite material together. In some embodiments, the carbonized precursor can be a substantially continuous phase. Thus, the carbonized precursor can be a structural material as well as an electrochemically active and conductive material. In some embodiments, the silicon particles and / or material particles added to the mixture are distributed throughout the composite material. In some embodiments, the silicon particles and / or other material particles can be uniformly distributed throughout the composite material to form a uniform composite material.

[0049] In some embodiments, the composite and / or electrode does not include more than a trace amount of polymer remaining after pyrolysis of the precursor. In further embodiments, the composite and / or electrode does not include a non-conductive binder. The composite may also include porosity. In some embodiments, the composite (or film) may include a volume porosity of about 1% to about 70% or about 5% to about 50%. For example, the porosity may be about 5% to about 40% by volume.

[0050] In some embodiments, the electrodes of the battery or electrochemical cell may comprise a composite material, including a composite material with silicon particles as described herein. For example, the composite material may be used for the anode and / or cathode. In some embodiments, the battery is a lithium-ion battery. In further embodiments, the battery is a secondary battery, or in other embodiments, the battery is a primary battery.

[0051] Furthermore, to enhance the life of the battery, the full capacity of the composite material of the electrodes described herein cannot be utilized during use of the battery (e.g., the number of charge / discharge cycles before the battery is damaged, or the performance of the battery drops below a usable level). For example, a composite material having about 70% by weight of silicon particles, about 20% by weight of carbon from a precursor, and about 10% by weight of graphite may have a maximum gravimetric capacity of about 3000 mAh / g, but the composite material can only be used at a maximum gravimetric capacity of about 550 to about 1500 mAh / g. Although the maximum gravimetric capacity of the composite material cannot be utilized, higher capacity than certain lithium-ion batteries can still be achieved when the composite material is used at a lower capacity. In some embodiments, the composite material is used at or only at a gravimetric capacity less than about 70% of the maximum gravimetric capacity of the composite material. For example, the composite material is not used at a gravimetric capacity greater than about 70% of the maximum gravimetric capacity of the composite material. In further embodiments, the composite material is used or is only used at a weight capacity of less than about 50% of the composite material's maximum weight capacity, or less than about 30% of the composite material's maximum weight capacity. EXAMPLES

[0052] The following examples are provided to illustrate the advantages of some embodiments of the electrodes, electrochemical cells, and methods of forming the same. These examples are discussed for illustrative purposes and should not be construed as limiting the scope of the disclosed embodiments.

[0053] Instead of forming the electrochemically active material on a substrate, removing the active material from the substrate, and depositing the active material on a current collector, various embodiments described herein can simplify the manufacturing process by pyrolyzing the active material on the current collector (e.g., in various embodiments, directly on the current collector). Example coin cells were made using standard cathodes, standard electrolytes, and anodes formed using various embodiments described herein. Such coin cells were compared to coin cells made using standard cathodes, standard electrolytes, and anodes formed by laminating pyrolyzed materials (e.g., pre-pyrolyzed materials) onto copper or stainless steel current collectors. Table I includes the test conditions for the various samples.

[0054] [Table 1]

[0055] Figure 4 is a plot of discharge capacity as a function of cycle number for various samples. Every 50 cycles was plotted to produce Figure 5, which is a plot of IEC (International Electrotechnical Commission) capacity as a function of cycle number. As shown, the samples including anodes formed by coating and pyrolyzing the active material on a stainless steel current collector showed the highest capacity compared to samples where the anode was first formed and then laminated onto a copper or stainless steel current collector.

[0056] Various embodiments have been described above. Although the present invention has been described with reference to these specific embodiments, the description is intended to be illustrative and not restrictive. Various modifications and applications may occur to those skilled in the art without departing from the true spirit and scope of the invention as defined in the appended claims. [Explanation of symbols]

[0057] 100 Method for forming an electrode 110 Process of preparing a current collector 120 Supplying the mixture onto a current collector 130 A process for pyrolyzing the mixture on the current collector

Claims

1. A current collector; and Composite material on current collector wherein the composite material comprises one or more carbon phases as a substantially continuous phase with silicon particles distributed throughout the composite material; the one or more types of carbon phases include hard carbon; An electrode, wherein the amount of said hard carbon is 10-25% by weight of said composite material.

2. The electrode of claim 1 , wherein the silicon particles comprise micrometer-sized silicon particles.

3. 10. The electrode of claim 1 , wherein the current collector comprises copper.

4. The electrode of claim 1 , wherein the composite material is adhered to a current collector.

5. 10. The electrode of claim 1, wherein the current collector is made of a material in which one or more carbon phases and silicon particles do not adversely react with the current collector.

6. The electrode of claim 1 , wherein the current collector comprises a metal foil.

7. The electrode of claim 1 further comprising a polymer.

8. The electrode of claim 1 further comprising an active material.

9. 10. The electrode of claim 1, wherein the current collector comprises a current collector coated with a polymer on at least one side of the current collector, and the composite material is on at least one side of the current collector comprising the polymer.

10. 10. The electrode of claim 1, wherein the current collector comprises a current collector coated with a carbon film on at least one side of the current collector, and the composite material is on at least one side of the current collector comprising the carbon film.

11. 11. The electrode according to any one of the preceding claims, wherein the silicon particles have a particle size between 10 nm and 50 μm.

12. The electrode according to any one of claims 1 to 11, wherein the composite material further comprises conductive particles and / or graphite.

13. A battery comprising an electrode according to any one of claims 1 to 12.

14. A current collector; and Composite material on current collector wherein the composite material comprises one or more carbon phases as a substantially continuous phase with silicon particles distributed throughout the composite material; the one or more types of carbon phases include hard carbon; the amount of said hard carbon being 10-25% by mass of said composite material; an electrode, wherein the composite material is formed on and adhered to the current collector by converting the precursor to one or more carbon phases by pyrolysis of a mixture including a precursor and silicon particles on the current collector.

15. A current collector; and Composite material on current collector wherein the composite material comprises one or more carbon phases as a substantially continuous phase with silicon particles distributed throughout the composite material; an electrode, wherein the composite material is formed on and adhered to the current collector by converting the precursor to one or more carbon phases by pyrolysis of a mixture including a precursor and silicon particles on the current collector.